Method for thermal surface post-crosslinking of superabsorbents
By spraying a post-crosslinking agent solution onto the surface in a contact dryer and controlling the direction and speed of the exhaust gas flow, the problems of high TOC load and uneven coating during the hot surface post-crosslinking process of superabsorbents were solved, resulting in a more efficient coating effect and improved performance.
Patent Information
- Application Number
- CN202480053054.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-18
- Filing Date
- 2024-08-07
- Publication Date
- 2026-03-20
AI Technical Summary
Existing technologies, when performing thermal surface crosslinking on superabsorbents, result in a high amount of organic matter entrained in the exhaust gas, leading to excessively high TOC load and uneven coating.
The superabsorbent particles are thermally surface-crosslinked by spraying a surface crosslinking agent solution. This is achieved by spraying a solution with an average droplet diameter of 100 to 4,500 µm in a contact dryer, and deflecting the waste gas flow upwards by at least 75° relative to the horizontal product flow direction, with a waste gas flow velocity of less than 5 m/s, in order to control the amount of organic matter entrained in the waste gas and the uniformity of the coating.
It effectively reduced the TOC load in the exhaust gas, improved the uniformity of the coating, and enhanced the absorption and centrifugal retention capacity of the superabsorbent.
Abstract
Description
[0001] The present invention relates to a method for continuous thermal surface postcrosslinking of superabsorbents, wherein superabsorbent particles are coated by spraying a surface postcrosslinker solution, the average droplet diameter at spraying is from 100 to 4,500 pm, the coated superabsorbent particles are subjected to thermal surface postcrosslinking in a contact dryer 1, a gas is passed into the contact dryer 1, an exhaust gas stream is discharged from the contact dryer 1, the exhaust gas stream is deflected upwards by at least 75° relative to the horizontal product flow direction in the contact dryer 1, and the exhaust gas stream has a gas flow velocity of less than 5 m / s immediately after deflection.
[0002] Superabsorbents are used for the manufacture of diapers, sanitary tampons, sanitary napkins and other hygiene articles, but also as water-retaining agents in horticulture. Superabsorbents are also known as water-absorbing polymers.
[0003] The preparation of superabsorbents is described in the monograph "Modern Superabsorbent Polymer Technology", F. L. Buchholz and A. T. Graham, Wiley-VCH, 1998, pages 71 to 103.
[0004] In order to improve application properties, such as liquid conductivity (SFC - saline flow conductivity) and absorbency under a pressure of 49.2 g / cm2(AUHL - absorbency under high load), superabsorbent particles are usually surface postcrosslinked. By this, the degree of crosslinking of the particle surface is increased, so that the absorbency under a pressure of 49.2 g / cm2(AUHL) and the centrifuge retention capacity (CRC) can be at least partially decoupled. This surface postcrosslinking can be carried out in an aqueous gel phase. Preferably, however, the surface postcrosslinker is applied to the surface of dried, ground and sieved polymer particles (base polymer) and subjected to thermal post-surface crosslinking. Suitable crosslinkers are compounds which are capable of forming covalent bonds with at least two carboxyl groups of the polymer particles.
[0005] It is an object of the present invention to provide an improved method for the thermal surface postcrosslinking of superabsorbent particles, in particular to achieve a lower TOC load in the exhaust gas.
[0006] This objective is achieved by a method for continuous hot surface post-crosslinking of superabsorbents, wherein superabsorbent particles are coated by spraying a surface post-crosslinking agent solution, the coated superabsorbent particles are subjected to heat post-treatment in a contact dryer 1, and the heat-treated superabsorbent particles are cooled in a contact dryer 2. The method is characterized by an average droplet diameter of 100 to 4,500 µm during spraying, the introduction of gas into the contact dryer 1, the discharge of waste gas from the contact dryer 1, the waste gas flow being deflected upwards by at least 75° relative to the horizontal product flow direction in the contact dryer 1, and the immediate gas velocity of the waste gas flow after deflection being less than 5 m / s.
[0007] Contact dryers suitable for the continuous method of the present invention are, for example, paddle dryers and disc dryers. In a contact dryer, the material to be dried is conveyed and tumbled along a heated surface by a power tool. Contact dryers can also be used for cooling.
[0008] The average droplet diameter of the surface post-crosslinking agent solution during spraying is preferably 150 to 3,500 µm, more preferably 200 to 2,500 µm, particularly preferably 250 to 1,500 µm, even more preferably 300 to 1,250 µm, and especially preferably 350 to 1,000 µm. The average droplet diameter can be determined by light scattering. The average droplet diameter is also known as the average volume diameter (MVD) or D. V0.5 Or average mass diameter (MMD).
[0009] For nozzles, droplet size is directly related to flow rate; that is, as the flow rate increases, the droplet size decreases. Droplet size also decreases as the initial nozzle pressure or the spray angle increases.
[0010] The spraying of the surface crosslinking agent solution is not subject to any other restrictions. For example, hydraulic nozzles and dual-fluid nozzles can be used. Hydraulic nozzles are preferred.
[0011] The waste gas flow is preferably deflected upwards by 75 to 105° relative to the horizontal product flow direction in the contact dryer 1, more preferably by 80 to 100°, and particularly preferably by 85 to 95°.
[0012] The gas velocity immediately after deflection is preferably less than 2 m / s, more preferably less than 1 m / s, particularly preferably less than 0.5 m / s, and even more particularly preferably less than 0.3 m / s.
[0013] For example, the gas flow rate of the waste gas stream can be adjusted by adjusting the diameter of the dome on the contact dryer 1.
[0014] This invention is based on the understanding that excessively small droplet size combined with excessively high exhaust gas velocity leads to an increase in the amount of organic matter entrained, resulting in a rise in the TOC value of the exhaust gas. Conversely, excessively large droplet size leads to uneven coating.
[0015] The preferred temperature for spraying the superabsorbent particles onto the surface after crosslinking agent is 30°C to 80°C, particularly preferably 35°C to 75°C, and even more preferably 40°C to 70°C.
[0016] Based on the superabsorbent particles, the surface post-crosslinking agent solution contains preferably 0.001 wt% to 2 wt%, particularly preferably 0.01 wt% to 1 wt%, and even more particularly preferably 0.03 wt% to 0.7 wt% of surface post-crosslinking agent. Based on the superabsorbent particles, the surface post-crosslinking agent solution also contains preferably 0.5 wt% to 5 wt%, particularly preferably 1.0 wt% to 4 wt%, and even more particularly preferably 1.5 wt% to 3 wt% of water.
[0017] The superabsorbent particles are heated in the contact dryer 1 to a temperature preferably from 110°C to 220°C, particularly preferably from 120°C to 210°C, and even more preferably from 130°C to 200°C. The residence time of the superabsorbent particles in the contact dryer 1 is preferably from 10 to 60 minutes, more preferably from 15 to 50 minutes, and particularly preferably from 20 to 40 minutes.
[0018] Auxiliary heating and / or thermal isolation can be provided for the contact dryer 1 and its connection to the contact dryer 2.
[0019] The superabsorbent particles are cooled in the contact dryer 2 to a temperature preferably from 30°C to 80°C, particularly preferably from 35°C to 70°C, and even more preferably from 40°C to 60°C. The residence time of the superabsorbent particles in the contact dryer 2 is preferably from 10 minutes to 60 minutes, particularly preferably from 15 minutes to 50 minutes, and even more preferably from 20 minutes to 40 minutes.
[0020] In a preferred embodiment of the invention, the gas flow introduced into the contact dryer 1 has an oxygen content of less than 10 vol%. For example, the gas flow rate per m³ of the internal volume of the contact dryer 1 is 5 to 60 Nm³ / h, preferably 10 to 50 Nm³ / h, more preferably 15 to 40 Nm³ / h, and particularly preferably 20 to 30 Nm³ / h. 1 Nm³ corresponds to a gas volume of 1 m³ under the conditions of 273.15 K and 1,013.25 hPa.
[0021] The preparation of superabsorbents will be described in detail below.
[0022] Superabsorbents are prepared by polymerizing monomer solutions and are typically insoluble in water.
[0023] The olefinic unsaturated monomer carrying the acid group preferably has water solubility, that is, its solubility in water at 23°C is generally at least 1 g / 100 g water, preferably at least 5 g / 100 g water, particularly preferably at least 25 g / 100 g water, and even more particularly preferably at least 35 g / 100 g water.
[0024] Suitable monomers include, for example, olefinic unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and itaconic acid. Particularly preferred monomers are acrylic acid and methacrylic acid. Acrylic acid is even more particularly preferred.
[0025] Unsaturated olefinic monomers carrying acid groups are typically partially neutralized. Neutralization is carried out at the monomer stage. This is usually achieved by incorporating a neutralizing agent in aqueous or preferably solid form. The degree of neutralization is preferably 40 mol% to 85 mol%, particularly preferably 50 mol% to 80 mol%, and even more preferably 60 mol% to 75 mol%, wherein commonly used neutralizing agents can be used, preferably alkali metal hydroxides, alkali metal oxides, alkali metal carbonates or alkali metal bicarbonates and mixtures thereof. Ammonium salts, rather than alkali metal salts, can also be used. Particularly preferred alkali metals are sodium and potassium, but even more particularly preferred are sodium hydroxide, sodium carbonate or sodium bicarbonate and mixtures thereof, especially sodium hydroxide.
[0026] Monomers typically contain polymerization inhibitors, and preferably contain hydroquinone semiethers, which act as storage stabilizers.
[0027] Suitable crosslinking agents are compounds having at least two suitable crosslinking groups. Such groups include, for example, olefinic unsaturated groups capable of free radical polymerization into the polymer chain, and functional groups capable of forming covalent bonds with the acid groups of the monomer. Furthermore, polyvalent metal salts capable of forming coordination bonds with at least two acid groups of the monomer are also suitable as crosslinking agents.
[0028] Suitable crosslinking agents include, for example, ethylene glycol dimethacrylate, diethylene glycol diacrylate, polyethylene glycol diacrylate, allyl methacrylate, trimethylolpropane triacrylate, triallylamine, tetraallyl ammonium chloride, and tetraallylpropoxyethane as described in EP 0 530 438 A1, such as diacrylates and triacrylates described in EP 0 547 847 A1, EP 0 559 476 A1, EP 0 632 068 A1, WO 93 / 21237 A1, WO 03 / 104299 A1, WO 03 / 104300 A1, WO 03 / 104301A1 and DE 103 31 450 A1, such as DE 103 31 456 A1 and DE103 55 401. Mixed acrylates containing olefinic unsaturated groups in addition to acrylate groups as described in A1, or mixtures of crosslinking agents as described, for example, in DE 195 43 368 A1, DE 196 46 484 A1, WO 90 / 15830 A1 and WO 02 / 032962 A2.
[0029] Based on the total amount of monomers used, the amount of crosslinking agent is preferably from 0.05 wt% to 1.5 wt%, particularly preferably from 0.1 wt% to 1 wt%, and even more particularly preferably from 0.15 wt% to 0.6 wt%. As the crosslinking agent content increases, the centrifugal retention capacity (CRC) decreases, and the absorbability (AUL) at a pressure of 21.0 g / cm² reaches its maximum value.
[0030] All compounds that generate free radicals under polymerization conditions can be used as initiators, such as thermal initiators, redox initiators, and photoinitiators. Suitable redox initiators include sodium persulfate / ascorbic acid, hydrogen peroxide / ascorbic acid, sodium persulfate / sodium bisulfite, and hydrogen peroxide / sodium bisulfite. A mixture of a thermal initiator and a redox initiator, such as sodium persulfate / hydrogen peroxide / ascorbic acid, is preferred. Preferably, the disodium salt of 2-hydroxy-2-sulfinacetic acid, or a mixture of the sodium salt of 2-hydroxy-2-sulfinacetic acid, the disodium salt of 2-hydroxy-2-sulfinacetic acid, and sodium bisulfite, is used as the reducing component. Commercially available mixtures of this type include Brüggolite® FF6 and Brüggolite® FF7 (Brüggemann Chemicals; Heilbronn; Germany).
[0031] The water content of the monomer solution is preferably from 40 wt% to 75 wt%, particularly preferably from 45 wt% to 70 wt%, and even more preferably from 50 wt% to 65 wt%. As the water content increases, the energy consumption in the subsequent drying process increases, and if the water content decreases, the heat of polymerization may not be fully dissipated.
[0032] The temperature of the monomer solution is preferably from 10°C to 90°C, particularly preferably from 20°C to 70°C, and even more particularly preferably from 30°C to 50°C.
[0033] To achieve optimal results, the preferred polymerization inhibitor requires dissolved oxygen. Therefore, dissolved oxygen in the monomer solution can be removed before polymerization by inerting, preferably by passing an inert gas such as nitrogen or carbon dioxide through it. Preferably, the oxygen content of the monomer solution is reduced to less than 1 wppm before polymerization, particularly preferably to less than 0.5 wppm, and even more preferably to less than 0.1 wppm.
[0034] Suitable reactors for polymerization include, for example, kneading reactors or belt reactors. In a kneader, the polymer gel produced during the polymerization of an aqueous monomer solution or suspension is continuously pulverized by, for example, a counter-clockwise rotating stirring shaft, as described in WO 2001 / 038402 A1. Polymerization in a belt reactor has been described, for example, in DE 38 25 366 A1 and US 6,241,928. Polymerization in a belt reactor produces a polymer gel that must be pulverized, for example, in an extruder or kneader.
[0035] To improve drying performance, the pulverized polymer gel obtained by kneading can be additionally extruded.
[0036] Subsequently, the polymer gel is typically dried using a belt dryer with circulating air until the moisture content is preferably 0.5 wt% to 10 wt%, particularly preferably 1 wt% to 7 wt%, and even more particularly preferably 2 wt% to 5 wt%, wherein the remaining moisture content is determined according to EDANA's recommended test method No. WSP 230.2-05 "Mass Loss Upon Heating". If the remaining moisture content is too high, the dried polymer gel will have an excessively low glass transition temperature T0. g Furthermore, it is difficult to process further. If the residual moisture is too low, the dried polymer gel becomes too brittle, and an undesirable large number of excessively small ("fines") polymer particles are produced in the subsequent pulverization step. The polymer gel has a solids content of preferably 25 wt% to 90 wt%, particularly preferably 35 wt% to 70 wt%, and even more particularly preferably 40 wt% to 60 wt% before drying. The dried polymer gel is then broken up, and optionally coarsely pulverized.
[0037] The dried polymer gel is then typically ground and sorted, which can usually be done using a single or multi-stage roller mill (preferably a two- or three-stage roller mill), pin mill, hammer mill, or vibratory mill.
[0038] The average particle size of the polymer particles separated as the product fraction is preferably at least 150 µm to 850 µm, particularly preferably 250 µm to 600 µm, and even more particularly preferably 300 µm to 500 µm. The average particle size of the product fraction can be determined using EDANA's recommended test method No. WSP 220.2 (05) "Partikel Size Distribution," in which the mass proportions of the sieve fraction are cumulatively plotted, and the average particle size is determined graphically. Here, the average particle size is the mesh width value corresponding to a cumulative 50 wt%.
[0039] To further improve properties, the polymer particles are thermally surface-crosslinked. Suitable surface-crosslinking agents are compounds containing groups capable of forming covalent bonds with at least two carboxyl groups of the polymer particles. Suitable compounds include, for example, polyfunctional amines, polyfunctional aminoamines, and polyfunctional epoxides as described in EP 0 083 022 A2, EP 0 543 303 A1, and EP 0 937 736 A2; difunctional or polyfunctional alcohols as described in DE 33 14 019 A1, DE 35 23 617 A1, and EP 0 450 922 A2; or β-hydroxyalkylamides as described in DE 102 04 938 A1 and US 6,239,230.
[0040] In a preferred embodiment of the invention, in addition to the surface crosslinking agent, polyvalent cations are also applied to the particle surface.
[0041] The polyvalent cations applicable to the methods of this invention are, for example, divalent cations such as those of zinc, magnesium, calcium, and strontium; trivalent cations such as those of aluminum, iron, chromium, rare earth elements, and manganese; and tetravalent cations such as those of titanium and zirconium. Possible counterions include chlorides, bromides, hydroxides, sulfates, bisulfates, carbonates, bicarbonates, nitrates, phosphates, hydrogen phosphates, dihydrogen phosphates, and carboxylates such as acetates and lactates. Aluminum hydroxide, aluminum sulfate, and aluminum lactate are preferred.
[0042] Based on the polymer, the amount of polyvalent cation used is, for example, 0.001 wt% to 1.5 wt%, preferably 0.005 wt% to 1 wt%, and particularly preferably 0.02 wt% to 0.8 wt%.
[0043] Post-crosslinking was performed by spraying a post-crosslinking agent solution onto dried polymer particles. After spraying, the polymer particles coated with the post-crosslinking agent were heat-treated.
[0044] The surface post-crosslinking agent solution is preferably sprayed in a mixer with a moving agitator, such as a spiral mixer, disc mixer, or paddle mixer. Horizontal mixers, such as paddle mixers, are particularly preferred, and vertical mixers are even more preferred. The difference between horizontal and vertical mixers lies in the support method of the agitator shaft; that is, horizontal mixers have a horizontally supported agitator shaft, while vertical mixers have a vertically supported agitator shaft. Suitable mixers include, for example, Horizontale Pflugschar® Mischer (Gebr. Lödige Maschinenbau GmbH; Paderborn; Germany), Vrieco-Nauta Continuous Mixer (Hosokawa Micron BV; Duttingheim; Netherlands), Processall Mixmill Mixer (Processall Incorporated; Cincinnati; USA), and SchugiFlexomix® (Hosokawa Micron BV; Duttingheim; Netherlands). However, the surface post-crosslinking agent solution can also be sprayed in a fluidized bed.
[0045] Post-crosslinking agents are typically used as aqueous solutions. The penetration depth of the post-crosslinking agent into the polymer particles can be adjusted by utilizing the content of non-aqueous solvents or the total solvent volume.
[0046] The hot surface crosslinking is carried out in contact dryers, particularly preferably in paddle dryers, and even more preferably in disc dryers. Suitable dryers include, for example, the Hosokawa Bepex® Horizontal PaddleDryer (Hosokawa Micron GmbH; Rheingarten; Germany), the Hosokawa Bepex® Disc Dryer (Hosokawa Micron GmbH; Rheingarten; Germany), the Holo-Flite® dryers (Metso MineralsIndustries Inc.; Danville; USA), and the Nara Paddle Dryer (NARA Machinery Europe; Frasen; Germany).
[0047] The post-crosslinked polymer particles can then be reclassified, wherein excessively small and / or excessively large polymer particles are separated and fed back into the method.
[0048] To further improve properties, the post-crosslinked polymer particles on the surface can be coated or re-wetted.
[0049] Rewetting is preferably performed at a temperature between 30°C and 80°C, particularly preferably between 35°C and 70°C, and even more preferably between 40°C and 60°C. At excessively low temperatures, polymer particles tend to aggregate, while at higher temperatures, water evaporates significantly. The amount of water used for rewetting is preferably 1 wt% to 10 wt%, particularly preferably 2 wt% to 8 wt%, and even more preferably 3 wt% to 5 wt%. Rewetting enhances the mechanical stability of the polymer particles and reduces their tendency to become electrostatically charged. Preferably, rewetting is performed in a cooler after post-crosslinking on the hot surface.
[0050] Coatings suitable for improving swelling ratio and gel bed permeability (GBP) include, for example, inorganic inert substances (such as water-insoluble metal salts), organic polymers, cationic polymers, and divalent or polyvalent metal cations. Coatings suitable for binding dust include, for example, polyols. Coatings suitable for resisting the undesirable agglomeration tendency of polymer particles include, for example, fumed silica (such as Aerosil® 200), precipitated silica (such as Sipernat® D17), and surfactants (such as Span® 20).
[0051] method:
[0052] Unless otherwise specified, all measurements were performed at an ambient temperature of 23 ± 2 °C and a relative humidity of 50 ± 10%. The superabsorbent particles were thoroughly mixed before measurement.
[0053] Saline flow conductivity
[0054] Liquid conductivity (SFC) was determined according to the test method “Urine Permeability Measurement (UPM) Test method” described on pages 19 to 22 of EP 2 535 698 A1. Example
[0055] The monomer solution was prepared by continuously mixing deionized water, 50 wt% sodium hydroxide solution, and acrylic acid, resulting in a neutralization degree of 71.0 mol%. The water content of the monomer solution was 58.25 wt%.
[0056] 3-ethoxylated glycerol triacrylate (approximately 85 wt%) was used as a crosslinking agent. The dosage was 1.04 kg per ton of monomer solution.
[0057] Citric acid was used as the complexing agent. The dosage was 0.07 kg per ton of monomer solution.
[0058] To initiate free radical polymerization, 1.38 kg of 0.25 wt% aqueous hydrogen peroxide solution, 3.22 kg of 15 wt% aqueous sodium persulfate solution, and 1.04 kg of 1 wt% aqueous ascorbic acid solution were added to each ton of monomer solution.
[0059] The monomer solution was fed into a List Contikneter reactor (LISTAG, Ariesdorf, Switzerland) with a volume of 6.3 m³. The throughput of the monomer solution was approximately 22.5 t / h. The temperature of the reaction solution at the inlet was 30 °C.
[0060] Between the points where the crosslinking agent is added and where the hydrogen peroxide and sodium persulfate solution are added, the monomer solution is inerted using nitrogen gas. Ascorbic acid is then added directly to the reactor.
[0061] After approximately 50% of the residence time, approximately 1,000 kg / h of polymer particles smaller than 150 µm, resulting from the crushing and sorting during the preparation process, are additionally added to the reactor. The residence time of the reaction mixture in the reactor is approximately 15 minutes.
[0062] The resulting polymer gel is conveyed onto the conveyor belt of a circulating air belt dryer via a vibrating conveyor belt. This circulating air belt dryer is 48 m long, and its conveyor belt has an effective width of 4.4 m. The aqueous polymer gel is continuously dried in the circulating air belt dryer using an air / gas mixture (approximately 175°C). The residence time in the circulating air belt dryer is approximately 37 minutes.
[0063] The dried polymer gel was pulverized using a three-stage roller mill and sieved to a particle size of 150µm to 850µm. Polymer particles smaller than 150µm were separated. Polymer particles larger than 850µm were returned for further pulverization. The polymer particles in the 150µm to 850µm size range were then subjected to thermal surface post-crosslinking.
[0064] These polymer particles were coated with a surface post-crosslinking agent solution in a Schugi Flexomix® (Hosokawa Micron BV, Duttingheim, Netherlands) and then dried at 186.5°C for 45 minutes in a Nara paddle dryer (GMF Gouda, Waddingsfin, Netherlands).
[0065] A crosslinking agent solution is used for coating after spraying the surface in Schugi Flexomix®. The average droplet diameter is approximately 750 μm.
[0066] Add the following amounts of material to Schugi Flexomix®:
[0067] 9.5t / h polymer particles
[0068] 366.7 kg / h surface crosslinking agent solution
[0069] The surface post-crosslinking agent solution contains 1.55 wt% 2-hydroxyethyl-2-oxazolidinone, 1.55 wt% 1,3-propanediol, 12.95 wt% 1,2-propanediol, 10.88 wt% aluminum lactate, 50.70 wt% water, 22.28 wt% isopropanol, and 0.08 wt% sorbitan laurate (Span®20).
[0070] The Nara Paddle Dryer has an internal volume of 18.8 m³. Approximately 370 Nm³ / h of a nitrogen / oxygen mixture with an oxygen content of approximately 8 vol% is introduced into the Nara Paddle Dryer via the SchugiFlexomix®. An additional approximately 80 Nm³ / h of nitrogen is introduced at the end of the dryer. Exhaust gas, primarily containing water and isopropanol, is discharged vertically upwards through the dryer's dome, with an immediate gas velocity of 0.29 m / s after deflection. The dome has a diameter of approximately 1.6 m. The total exhaust gas volume at 186.5°C is approximately 2,100 m³ / h.
[0071] Superabsorbent particles, after surface post-crosslinking treatment, fall into the hopper through an overflow weir. At the lower end of the hopper is an impeller rotary valve.
[0072] The surface-crosslinked polymer particles were conveyed via a rotary impeller valve to a Nara paddle cooler (GMF Gouda, Waddingsfin, Netherlands) and cooled to approximately 60°C. During this process, the surface-crosslinked polymer particles were coated with an aqueous solution at a rate of 118.75 kg / h.
[0073] The obtained superabsorbent particles were packed into flexible medium-sized bulk containers (FIBCs) and analyzed. The superabsorbent flux density (SFC) was approximately 50 x 10⁻⁶. -7 cm³s / g.
[0074] When the average droplet size of the post-crosslinking agent solution in Schugi Flexomix® is less than 100 µm, and the immediate gas velocity of the exhaust gas in the Nara paddle dryer after deflection exceeds 5 m / s, the TOC value in the exhaust gas will increase. When the average droplet size of the post-crosslinking agent solution in Schugi Flexomix® is greater than 4,500 µm, the polymer particles will be unevenly coated.
Claims
1. A method for continuous thermal surface crosslinking of a superabsorbent, wherein, Superabsorbent particles are coated with a crosslinking agent solution after spraying, the coated superabsorbent particles are subjected to heat post-treatment in a contact dryer 1, and the heat-treated superabsorbent particles are cooled in a contact dryer 2. The method is characterized by an average droplet diameter of 100 to 4,500 µm during spraying, gas being introduced into the contact dryer 1, and waste gas being discharged from the contact dryer 1. The waste gas is deflected upwards by at least 75° relative to the horizontal product flow direction in the contact dryer 1, and the immediate gas velocity of the waste gas after deflection is less than 5 m / s.
2. The method according to claim 1, characterized in that, The immediate gas velocity after deflection is less than 0.5 m / s.
3. The method according to any one of claims 1 to 2, characterized in that, Partially neutralized, cross-linked polyacrylic acid is used as a superabsorbent.
4. The method according to any one of claims 1 to 3, characterized in that, The surface post-crosslinking agent is a compound that can form covalent bonds with the superabsorbent.
5. The method according to any one of claims 1 to 4, characterized in that, The surface post-crosslinking agent solution has an average droplet diameter of 250 to 1,500 µm during spraying.
6. The method according to any one of claims 1 to 5, characterized in that, The temperature during the spraying of the superabsorbent particles onto the surface with the crosslinking agent solution is between 30°C and 80°C.
7. The method according to any one of claims 1 to 6, characterized in that, The surface post-crosslinking agent solution contains 0.001 to 2 wt% of surface post-crosslinking agent relative to the superabsorbent particles.
8. The method according to any one of claims 1 to 7, characterized in that, The surface post-crosslinking agent solution contains 0.5 to 5 wt% water relative to the superabsorbent particles.
9. The method according to any one of claims 1 to 8, characterized in that, The superabsorbent particles are heated to a temperature of 110°C to 220°C in the contact dryer 1.
10. The method according to any one of claims 1 to 9, characterized in that, The residence time of the superabsorbent particles in the contact dryer 1 is 10 to 60 minutes.
11. The method according to any one of claims 1 to 10, characterized in that, The contact dryer 1 and its connection to the contact dryer 2, along with the hopper and feeding equipment, can be subjected to accompanying heating and / or thermal isolation.
12. The method according to any one of claims 1 to 11, characterized in that, The superabsorbent particles are cooled to a temperature of 30°C to 80°C in the contact dryer 2.
13. The method according to any one of claims 1 to 12, characterized in that, The residence time of the superabsorbent particles in the contact dryer 2 is 10 to 60 minutes.
14. The method according to any one of claims 1 to 13, characterized in that, The airflow has an oxygen content of less than 10 vol%.
15. The method according to claim 14, characterized in that, Gas is introduced into the contact dryer 1, and the total gas flow rate per m³ of the internal volume of the contact dryer 1 is 5 to 60 Nm³ / h.
Citation Information
Patent Citations
Process for post-crosslinking of a water absorbing polymer surface with a cyclic urea useful in foams, fibers, films, cables, especially sealing materials, liquid absorbing hygiene articles, packaging materials, and soil additives
DE10204938A1
(Meth)acrylic acid esters of monoalkoxylated polyols and their preparation
DE10331450A1
(Meth)acrylic acid esters of alkoxylated unsaturated polyol ethers and their preparation
DE10331456A1
(Meth)acrylic acid esters of unsaturated amino alcohols and their preparation
DE10355401A1
Water-absorbing polymers with improved properties, processes for their production and their use
DE19543368A1
